2018
DOI: 10.1289/isesisee.2018.p02.0900
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Facemasks on Airway Inflammation and Endothelial Dysfunction in Healthy Young Adults: A Double-Blind, Randomized, Controlled Crossover Study

Abstract: Background: Facemasks are increasingly worn during air pollution episodes in China, but their protective effects are poorly understood. We aimed to evaluate the filtration efficiencies of N95 facemasks and the cardiopulmonary benefits associated with wearing facemasks during episodes of pollution. Results: We measured the filtration efficiencies of particles in ambient air of six types of N95 facemasks with a manikin headform. The most effective one was used in a double-blind, randomized, controlled crossover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
6
0
1
Order By: Relevance
“…42 Indeed, it is encouraging that a number of studies have shown that reduction of personal exposure to urban PM through use of facemasks has been accompanied by improvements in cardiovascular parameters. 42,[56][57][58]242 Indoor air purifiers also appear to have beneficial effects in this regard, especially in cities with high levels of pollution. 42,243 The long-term consequences of these short-term benefits need to be established.…”
Section: Discussionmentioning
confidence: 99%
“…42 Indeed, it is encouraging that a number of studies have shown that reduction of personal exposure to urban PM through use of facemasks has been accompanied by improvements in cardiovascular parameters. 42,[56][57][58]242 Indoor air purifiers also appear to have beneficial effects in this regard, especially in cities with high levels of pollution. 42,243 The long-term consequences of these short-term benefits need to be established.…”
Section: Discussionmentioning
confidence: 99%
“…There are various studies were performed regarding the respirators' performance [2][3][4][5][6][7][8][9][10][11]. For instance, Mueller et al concluded that both filter efficiency and proper respirator fitting into the face are vital to provide the optimal protection [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Masks can trap warm, moist air, leading to rashes or overheating [21] and potentially pathogen retention [22]. Additionally, respirators may increase resistance to breathing, which may contribute to potential cardiovascular effects [16,23,24]. Cloth masks, which are inexpensive and used commonly in underdeveloped regions, remove only 15% of particles of size typical of diesel engine emissions [25] and are far inferior to protection against fine particles than facemasks rated as N95 (defined as filtering ⩾95% of 0.3 µm particles under test conditions) [13,14,25].…”
Section: Background and Evidencementioning
confidence: 99%
“…Evidence that N95 facemask use has an impact on cardiopulmonary health is limited. Short-term (2 h) use reduced particle-associated airway inflammation [24] and improved measures of autonomic nervous function [8,28] and blood pressure [8] versus wearing no facemask. N95 facemask use reduced the decline in lung function associated with air pollution among traffic police in Nepal [27].…”
Section: Background and Evidencementioning
confidence: 99%
See 1 more Smart Citation